Training habits, motivation, quality of life and sport injuries in 12 to 15 years old basketball players - Sánchez-Jover, F.; Gómez, A. (Journal of Human Sport & Exercise, 2017)
Background: Previous studies of basketball injury have not been able to compare injury incidence and risk with their healthy habits. Purpose: To determine rates and risks of injury in Spanish boys and girls basketball players. Study Type: Descriptive epidemiology study. Methods: A survey was carried out on injuries produced in basketball players during the seasons 2006-07, 2007-08 and 2008-09, which included their type, incidence and treatment. There took part 217 players - 12 to years old -. They were given a questionnaire related to habits and sports injuries and the SF-36 v2 Health Questionnaire. Results: The injuries took place both while competition and training, being ankle sprain the most frequent injury in both cases. After ankle sprain; the prevailing injuries were sprain - luxation of the fingers and knee sprain. Most of the players who got injured were the base, the forward, and the guard. A 53 % had suffered some injury in the last three seasons, being falling off the most frequent cause. The incidence of injuries out of every 1000 hours of exhibition found in the study is 1.39. There have been found significant differences in the exposure to injuries at the outcome of skill circuits at Interval Training work during training hours. The mental component is an important factor to be considered in all caused injuries.